Measurement of capacity utilisation in Irish manufacturing-industry - Oreilly, L; Nolan, B (Economic & Social Studies, 1979)
This paper estimates capacity output for Irish manufacturing industry using the Wharton School linked-peaks method, updating an index produced in McMahon and Smyth (1974). It then presents a capacity output series using a production function approach. This approach involves estimating a production function and then replacing the actual values of the inputs with estimated full capacity levels. The estimated production function is of Cobb-Douglas form, using electricity consumption as a measure of capital input. The two capacity output series are then compared and are found to show similar fluctuations. Finally, some suggestions are made for improving the estimates of the production function.
Keywords: Manufacturing Industry; Ireland